Whale-watching in NSW: research to integrate the needs of whales, tourists and industry - Stamation, Kasey Anne (UNSW Sydney, 2009)
This thesis examines the human and animal dimensions of whale-watching and develops a framework for management of the humpback whale-watching industry in New South Wales (NSW), Australia. The short-term responses of humpback whales to whale-watching vessels during their southward migration on the south coast of NSW were assessed. The behavior of pods was recorded from commercial whale-watching vessels during tours and compared to pods in the absence of vessels observed from shore in the same area. Pod sizes and composition were typical of southward migrating whales. Calf pods were more sensitive to the presence of vessels than non-calf pods. Whilst there was a longer dive time and a greater percentage of time spent submerged by whales in the presence of vessels, there were no associated changes in respiration intervals. Some surface behaviours were suppressed in the presence of vessels. Surface-active behaviours were prevalent in this study which indicates that social interactions amongst conspecifics are common during the southern migration. Feeding pods were observed on 24.5% of all whale-watching trips and during 14% of all observations made from shore. South-eastern NSW is probably a significant supplemental feeding ground for migrating whales. Feeding behaviour did not alter in the presence of vessels but the time between feeding lunges increased when vessels were closer than 100 m and when more than one vessel was present. The demographics, expectations, experience and satisfaction of land-based and boat-based whale-watchers in NSW were assessed by a questionnaire to participants. Land-based whale-watchers had high and often unrealistic expectations about their whale-watching experience and were moderately satisfied. Boat-based whale-watchers had high, but often realistic expectations of their experience and were highly satisfied. Satisfaction was a function of the degree to which expectations were met, the proximity of whales, the numbers of whales, their behavioural displays and the level of information available on whales. Whale-watchers showed limited increase in their knowledge and conservation-oriented behaviours over the long term. Current education about whales requires better structure and clearer conservation objectives. This study identifies research, education and vessel management as three fundamental components for the sustainable management of the whale-watching industry, and makes recommendations incorporating these components.